RANCANG BANGUN SISTEM BUKA TUTUP PINTU AIR MINIATUR REGULATING WEIR BENDUNGAN MERANGIN BERBASIS MIKROKONTROLER ARDUINO DENGAN SENSOR WATER LEVEL - Prasetyo Rizky Arfan Sodiq; Raden Arief Setyawan; n/a Nurussa’adah (Jurnal Mahasiswa TEUB, 2023)
A dam is a building used as a barrier to retaining river water flow to form a reservoir with water reserves. Some of the uses of dams include irrigation, power generation, and flood control facilities. Most dams also have a section called a water gate, which functions to remove unwanted water gradually or continuously. Dams have different water levels every time due to climate and rainfall, This will affect the water discharge in the dam. The water level in the dam can be utilized to produce potential energy which will later be used for electricity generation. The water flow also affects the productivity of the electrical power that can be generated. Therefore, this research will design an open-close regulating weir water gate of a Merangin Dam miniature using a water level sensor and an Arduino microcontroller. The test is carried out using three water level sensors, each water level sensor has three states so in this research there will be 27 states to openclose the water gate system. Based on the test results, the HY-SRF05 water level sensor has an error range of 0,02% to 21,72% where the measured water level has a higher error when the water level is lower. The test of the YF-S201water flow sensor obtained results where the water level in the dam affects the water flow in the penstock, the higher the water level of the miniature dam, the greater the water discharge in the penstock. Water flow sensor measurements obtained the highest water discharge value of 5,43 liters/minute with an error of 6,77% at a water level of 25 cm in the dam. The test results show that the system of opening and closing the regulating weir water gate can work with the desired conditions and results.Key Words: Dam, Regulating Weir, Water Gate